Twenty-four-hour blood pressure and CSF biomarkers of Alzheimer’s disease and related dementias in a community cohort - Madeline Gibson; William T. O’Brien; Ella Rowsthorn; Katherine H. Franks; Lachlan Cribb; Marina Cavuoto; Beaudan Campbell-Brown; Ian Harding; Meng Law; Trevor T.-J. Chong; Stuart J. McDonald; Terence J. O’Brien; et al. (GeroScience, 2026)
Hypertension in midlife is associated with increased dementia risk, yet its relationship with early pathological changes of Alzheimer’s disease and related dementias (ADRD) remains unclear. Unlike office blood pressure (BP), 24-h ambulatory BP (ABPM) may better reflect cardiovascular risk, but associations between 24-h BP measures with ADRD biomarkers are unknown. This cross-sectional study examined associations between BP and cerebrospinal fluid biomarkers of ADRD in mid-to-late life. Dementia-free participants ( n = 77; mean age = 67 [SD, 6]; 39% women) from the community-based Brain and Cognitive Health (BACH) cohort underwent office and 24-h ABPM assessments to calculate mean BP, nocturnal dipping, blood pressure variability (BPV, coefficient of variation) across 24-h, awake and asleep periods. Participants also completed a lumbar puncture to assess ADRD biomarkers: Aβ42/Aβ40 ratio, phosphorylated tau at threonine 217 (pTau217), glial fibrillary acidic protein (GFAP), and neurofilament light chain (NfL). Linear regression models examined associations between BP and ADRD biomarkers, adjusting for age, sex, BMI, smoking, anti-hypertensive medication use, and APOE ε4 status. Higher 24-h and awake mean BP were associated with higher GFAP (24-h: per 1-SD unit increase, β = 1606.6 pg/mL, p = .03; awake: β = 1668.pg/mL, p = .03) and NfL (24-h: β = 172.3 pg/mL, p = .03; awake: β = 162.3 pg/mL, p = .04) levels. Elevated asleep BPV was associated with higher Aβ42/Aβ40 ratio ( β = 0.01, p = .01). No, other clear associations were identified for the other BP metrics ( p > .05 for all). Findings indicate that elevated BP is associated with neuronal injury and astrocytic reactivity, suggesting possible pathways through which BP may relate to neurodegenerative processes, independent of overt amyloid or tau.

Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

The Role of Verbal Fluency in the Cerebellar Cognitive Affective Syndrome Scale in Friedreich Ataxia - Louise A. Corben; Eliza Blomfield; Geneieve Tai; Hiba Bilal; Ian H. Harding; Nellie Georgiou-Karistianis; Martin B. Delatycki; Adam P. Vogel (The Cerebellum, 2024)
Cerebellar pathology engenders the disturbance of movement that characterizes Friedreich ataxia (FRDA), yet the impact of cerebellar pathology on cognition in FRDA remains unclear. Numerous studies have unequivocally demonstrated the role of the cerebellar pathology in disturbed cognitive, language and affective regulation, referred to as Cerebellar Cognitive Affective Syndrome (CCAS), and quantified by the CCAS-Scale (CCAS-S). The presence of dysarthria in many individuals with ataxia, particularly FRDA, may confound results on some items of the CCAS-S resulting in false-positive scores. This study explored the relationship between performance on the CCAS-S and clinical metrics of disease severity in 57 adults with FRDA. In addition, this study explored the relationship between measures of intelligibility and naturalness of speech and scores on the CCAS-S in a subgroup of 39 individuals with FRDA. We demonstrated a significant relationship between clinical metrics and performance on the CCAS-S. In addition, we confirmed the items that returned the greatest rate of failure were based on Verbal Fluency Tasks, revealing a significant relationship between these items and measures of speech. Measures of speech explained over half of the variance in the CCAS-S score suggesting the role of dysarthria in the performance on the CCAS-S is not clear. Further work is required prior to adopting the CCAS-S as a cognitive screening tool for individuals with FRDA.

Correction to: MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gómez; Andreas Thieme; et al. (The Cerebellum, 2023)

MR Imaging in Ataxias: Consensus Recommendations by the Ataxia Global Initiative Working Group on MRI Biomarkers - Gülin Öz; Sirio Cocozza; Pierre-Gilles Henry; Christophe Lenglet; Andreas Deistung; Jennifer Faber; Adam J. Schwarz; Dagmar Timmann; Koene R. A. Van Dijk; Ian H. Harding; Astrid Adarmes-Gomez; Andreas Thieme; et al. (The Cerebellum, 2023)
With many viable strategies in the therapeutic pipeline, upcoming clinical trials in hereditary and sporadic degenerative ataxias will benefit from non-invasive MRI biomarkers for patient stratification and the evaluation of therapies. The MRI Biomarkers Working Group of the Ataxia Global Initiative therefore devised guidelines to facilitate harmonized MRI data acquisition in clinical research and trials in ataxias. Recommendations are provided for a basic structural MRI protocol that can be used for clinical care and for an advanced multi-modal MRI protocol relevant for research and trial settings. The advanced protocol consists of modalities with demonstrated utility for tracking brain changes in degenerative ataxias and includes structural MRI, magnetic resonance spectroscopy, diffusion MRI, quantitative susceptibility mapping, and resting-state functional MRI. Acceptable ranges of acquisition parameters are provided to accommodate diverse scanner hardware in research and clinical contexts while maintaining a minimum standard of data quality. Important technical considerations in setting up an advanced multi-modal protocol are outlined, including the order of pulse sequences, and example software packages commonly used for data analysis are provided. Outcome measures most relevant for ataxias are highlighted with use cases from recent ataxia literature. Finally, to facilitate access to the recommendations by the ataxia clinical and research community, examples of datasets collected with the recommended parameters are provided and platform-specific protocols are shared via the Open Science Framework.

Longitudinal investigation of brain activation during motor tasks in Friedreich ataxia: 24-month data from IMAGE-FRDA - Rosita Shishegar; Ian H. Harding; Louisa P. Selvadurai; Louise A. Corben; Martin B. Delatycki; Gary F. Egan; Nellie Georgiou-Karistianis (Brain Structure and Function, 2022)

Longitudinal Increases in Cerebral Brain Activation During Working Memory Performance in Friedreich Ataxia: 24-Month Data from IMAGE-FRDA - Rosita Shishegar; Ian H. Harding; Louise A. Corben; Martin B. Delatycki; Elsdon Storey; Gary F. Egan; Nellie Georgiou-Karistianis (The Cerebellum, 2020)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)